PENGARUH NILAI BUDAYA ASIA DALAM KERAMAHTAMAHAN ASIA - B. Syarifuddin Latif (Universitas Nasional, 2019)
Asian hospitality has gained a reputation for excellence in quality of facilities and services over the past decade. The unique, lovely ways of Asian hospitality spring from its strong historical and cultural background. Asian cultures and their peoples have special hand-making skills and are detail orientated which can be seen from the products produced and services provided by Asian organizations. They have a strong cultural education in the sense of